How Does Crime-Specific Victimization Impact Fear of Crime in Urban China? The Role of Neighborhood Characteristics - Jing, Fengrui (International journal of offender therapy and comparative criminology, 2024)
Past research has failed to find consistent relationships between criminal victimization and fear of crime. Except for neighborhood disorder and crime rate, few studies have examined whether other neighborhood conditions matter the victimization—fear relationship. Using survey data in Guangzhou neighborhoods, the present analysis employs multinomial logistic regression models to examine whether neighborhood characteristics moderate the relationship between violent victimization and fear of violence, and between burglary victimization and fear of burglary, separately. Some aspects of the neighborhood environment do differentially influence victims’ and non-victims’ fear levels. Besides verifying the interaction effect of neighborhood disorder and victimization, the present study finds that neighborhood policing alleviates the harmful effect of violent victimization on fear, while collective efficacy fosters the harmful effect of burglary victimization on fear. This paper underscores the significance of the social context of urban China in explaining the interplay of neighborhood characteristics and victimization on fear of crime.